Pertanggungjawaban Platform E-Commerce Terhadap Penipuan Oleh Pelaku Usaha Terverifikasi Yang Mengakibatkan Kerugian Konsumen - Rasyid, Mohammad Haikal; Jannah, Ghina Rhoudotul; Fiana, Vinka Arzetta; Latisha, Najwa; Nurfajriana, Syifa; Sakti, Muthia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to explain the types and forms of liability held by e-commerce platforms in cases of fraud by verified business actors. This includes a legal analysis of the platform's liability towards aggrieved consumers. This can improve the liability mechanism, e-commerce platforms can build consumer trust. Consumers who feel protected are more likely to shop online, which in turn can increase transaction volume and profits for e-commerce platforms. The method used in this research is Juridical-Normative by conducting research sourced from literature and from the results of decisions related to the Law or commonly referred to as library legal research conducted by examining secondary materials only. The results of this study are that consumer protection in digital transactions in Indonesia is regulated by the GCPL and ITE Law. In the case of fraud in ordering roof tiles on Tokopedia, there is negligence on the part of Tokopedia and vendors that violate the law. Consumer rights according to the GCPL have been violated, so the responsibility is not only on the deceptive seller but also on Tokopedia as a platform provider. However, Tokopedia does not support its consumers in resolving this dispute.